Ativismo Judicial: entre a Efetividade e a Autocontenção - Wanderley Neto, João Bosco de Barros (2016)
This work aims the study of judicial activism and its relation to the effectiveness of constitutional norms, starting with the theoretical appraisal of the characteristics surrounding the effectiveness of constitutional requirements, the overlapping aspects in the realization of duty of these state - judiciary - and the effect on the legal system, particularly on the relationship limits and legitimacy in situations of high political-discretionary hue. Noteworthy is also the vision given to judicial activism as multidimensional element, which can put a meaning sometimes positive, sometimes negative, the result of analysis and performance interpretation and argumentative role played by the judiciary in applying the rules constitutional